Analisis Percakapan antara Orang Jawa Ngapak (Brebes) dengan Orang Jawa (Semarang) dalam Percakapan Daring WhatsApp - Azizi, Mohammad Sofwan; Sahari, Dariel Ramadhan; Neina, Qurrota Ayu; Yuniawan, Tommi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the communication characteristics of speakers of the Javanese Ngapak (Brebes) dialect and the Semarang dialect in online interactions conducted via WhatsApp. Using a descriptive qualitative approach, the research analyzes phonological, lexical, and communicative variations that appear in cross-dialect exchanges. The findings show that Ngapak speakers maintain open vowel pronunciations and use distinctive lexical items such as nyong and rika, while Semarang speakers tend to use front vowels and vocabulary such as aku, kowe, and the particle lho. Despite these linguistic differences, both speakers communicate effectively through meaning negotiation and socially equal interaction. The results indicate that dialectal differences do not impede communication; instead, they demonstrate dynamic socio-linguistic adaptation among contemporary Javanese speakers. This study contributes to sociolinguistic and intercultural communication research and provides practical insights for dialect awareness, language education, and regional language preservation in the digital era.